Magnetoresistive sensors in a new biomagnetic instrumentation for applications in gastroenterology - Paixao, Fabiano C. [UNESP]; Silva, Fabiano M.; Miranda, Jose R. de A. [UNESP]; Baffa, Oswaldo (IEEE, 2007)
Anisotropic Magnetoresistive (AMR) sensors shows a new possibility to detect magnetic fields produced by magnetic particles present in the gastrointestinal (GI) tract. A system that uses excitation and detection of magnetic field was developed using AMR sensor. A magnetic flux concentrator was also studied to increase the sensitivity of AMR in this work.